Evaluation of fluidic pitch links for rotor hub vibration controls - Zhang, J.; Scarborough, L.H.; Smith, E.C.; Rahn, C.D.; Jolly, M.R. (My University, 2014)
Researchers have been exploring the potential for fluidic pitch links to replace traditional rigid pitch links for rotorcraft vibration reduction. Previous studies showed that the hub vibratory loads of a medium-sized helicopter with an articulated rotor system in high speed flight condition could be affected by tailoring the fluidic pitch link impedance. The current research is intended to advance and expand studies of the fluidic pitch link concept. A free wake model is implemented in rotor aeroelastic modeling. The fluidic pitch links have been examined at low forward speed for the vehicle, the results show that they can achieve average 39% vibration reduction at advance ratio 0.15. Fluidic pitch links are also be evaluated on a light helicopter with a hingeless rotor system. Parametric studies of fluidic pitch link properties are conducted, and their effect on rotor hub vibratory loads is evaluated at both low and high forward speeds for its off-design performance. The results indicate that fluidic pitch links work very well at advance ratio of 0.30, and can reduce hub loads by average 45%. The fluidic pitch links are also compared with the active individual blade pitch controls. The simulation results show their performances, in terms of rotor hub vibration reductions are comparable.